Improving occupants' satisfaction with effective maintenance management of HVAC system in office buildings - Au-Yong, C.P.; Ali, A.S.; Ahmad, F. (Elsevier, 2014)
Office buildings are equipped with HVAC system to provide a comfortable working environment. However, the level of the occupants' productivity and comfort is highly influenced by the reliability of HVAC system's service. Thus, the proper maintenance of HVAC system is necessary to ensure the smooth operations of an organisation. This paper seeks to investigate the maintenance characteristics of HVAC system that affect occupants' satisfaction and subsequently establish a relationship between the characteristics and occupants' satisfaction through questionnaire surveys and interviews; and finally develop a regression model for prediction purpose. The findings reveal that the maintenance characteristics which influence occupants' satisfaction include the skill and knowledge of the manager, the skill and knowledge of the labourer, the quality of spare parts and materials, as well as the response level towards failure and downtime. The study concludes that an effective communication platform which involves all key participants in the maintenance activities should be developed by the management to improve the maintenance outcomes.